Protrusion of the device: a complication of catheter closure of patent ductus arteriosus - Ottenkamp, J (1992)
Objective—To assess the medium term results of percutaneous transvenous closure of patent ductus arteriosus, in particular with regard to protrusion of the device with or without turbulence of the bloodflow. Design—Clinical examination and echocardiographic study (cross sectional Doppler, and colour Doppler examination) within 24 hours of and at least 6 months after implantation (range 6–26 (mean 15) months). Setting—Multicentre study at the departments of paediatric cardiology of three academic hospitals. Tertiary clinical care of the first group of patients in the Netherlands treated by the percutaneous transvenous method. Patients—36 patients (12 male, 24 female) mean age 8·2 years, (range 1·7–58·3), mean weight 25·5 kg (range 11–67·8 kg). The total group consisted of 46 patients. In one the implantation had failed and nine others were not available for regular follow up. All 36 patients underwent non-surgical closure of the patent ductus arterisus with a Rashkind double umbrella prosthesis. Main outcome measures—Diagnosis or exclusion of protrusion of the Rashkind device with or without turbulence of the blood flow with follow up of changes in protrusion and turbulence. Results—In 17 patients the prosthesis protruded into an arterial lumen: the aorta in 13 and the (left) pulmonary artery in four, with turbulence in seven and two cases respectively. After six months the aortic protrusion disappeared in three, including one who had had turbulent blood flow. At the end of follow up the prosthesis still protruded into the aorta in 10 but in three the turbulence had vanished. In two of the three remaining patients with turbulence in the descending aorta the degree of turbulence had decreased. There was no lessening of turbulence in the four patients in whom the device protruded into the pulmonary artery. Conclusions—The Rashkind double umbrella can protrude into the descending aorta and the left pulmonary artery without causing turbulent blood flow. Turbulence and the protrusion itself can disappear. Endocarditis prophylaxis may be required for as long as the device causes turbulence.